Thermal analysis of hydrodynamic lubricated journal bearings in internal combustion engines. (September 2017) - Lorenz, Norbert; Offner, Günter; Knaus, Oliver
Hydrodynamic journal bearings are essential components in the internal combustion engines. The prediction of their reliability, durability, and economy, and also of their friction loss power and wear, are of highest importance. For an appropriate representation of the hydrodynamic load-carrying capacity and also the friction behavior, the multibody dynamics of the contacting components, the shape of the contacting component surfaces, the amount of the available lubricant, and the properties of the lubricant itself are of importance. A Reynolds-averaged equation with laminar flow conditions in combination with a dry asperity contact model and a multibody dynamic simulation of the structural components is a typical modeling approach for that purpose. Furthermore, this paper shows a newly developed model for the temperature distribution in the lubricant and the bearing structures. It includes thermal interface conditions between these domains, which incorporates the asperity energy source and predicts the temperature in supply areas. The presented method is applied for a typical engineering task of a sensitivity analysis for oils with different viscosity index improvers in a main bearing of a four-cylinder inline diesel engine. The influence of the oil film temperature on the oil film viscosity and, therefore, on the load-carrying capacity is shown. Furthermore, the simplified two-dimensional approach is compared with a three-dimensional approach in terms of the obtained result. The presented results show similar accuracy of the two-dimensional approach compared to the equivalent three-dimensional case.